The Effect of Corporate Action on Financial Performance in Transportation Sector - Yenny Hutomo; Juniarti Juniarti (Business Accounting Review, 2021)
There is many previous research that analyzed market responses towards mergers & acquisitions. However, there are limited research has been conducted in the transportation sector in ASEAN. This research investigates the effect of corporate action on investor response to transportation sector companies in ASEAN. Investor response was measured by cumulative abnormal returns (CAR), while corporate action we use a dummy variable to separate companies that perform M&A corporate action and those that did not perform M&A corporate action. Control variables used in this study including firm size, firm age, and firm leverage. The number of samples in this study was 192 companies in the transportation sector in ASEAN during the 2015-2020 period. The results showed that the independent variable corporate action had a negative effect on investor response. While the control variables firm size, firm age, and firm leverage had no significant effect on investor response.